Divan of Şuhi :|critical edition-textual analysis - Top, Yılmaz. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2003., 2003)
Şuhi is one of the hardly known poets of the 17th century which had taken over the accumulation of the classical Ottoman poetry and transported it to the 18th century with elegance and maturity. The sources inform us very little about his life; that is to say we do not know when he was born. In the 17th century, Rıza Tezkiresi was the only biography which mentioned about Şuhi and he was introduced as a poet "who is one of a kind" in this biography. In Vakâyiü'l-Fuzalâ that is a biographical work written in 18th century, the scholarly education of Şûhî and medrese schools he worked as a professor were told in detail. However, his private life was not followed up with interest in this biography. The aim of this study is to examine the single copy of Şûhî's Divan whose date of reduction is unknown according to form, style and content together with a transcription of the text. Also this research gives short information about his life and his literal personality. For this aim, limited information given by biographies has been collected and the other information about his literal personality has been brought out as much as possible from the poetries in his Divan. With the help of the meter and rhyme, the scribe's mistakes and misspellings have been evaluated with critically. Şûhî's Divan has been examined in three parts: content, form and style. Versification forms, meter, rhyme and repetiton of sound (redif) have been evaluated as form properties. In the content part; religious elements which exist in Divan (verses of the Koran and Hadiths, prophets and religious leaders) and mythological-historical people have been examined according to the reasons of mentioning in Divan. In the style evaluation part, idioms and proverbs which poet used, the plainness in the language, harmony and other poetical devices have been tried to studied. In the conclusion part, aspects of Şûhî's literal personality which had been lightened by Şûhî's Divan have been pointed out. The whole study ends with an index which has been prepared for compounds and proper nouns and also with a short bibliography.
Keywords: Turkish literature -- History and criticism.; Turkish poetry -- History and criticism.